Impact of the students´ scientific activity on the academic results of the subject Morpho-physiology III - Sandra Williams Serrano; Milagros León Regal; Judeny Coll Cañizares; Juan Andrés Alemañy Co (Medisur)
Foundation: Students scientific activity has a great important because practicing inductive and deductive thinking so as abilities development contributes to their comprehensive development. Objective: To determine the impact of the students’ scientific activity quality on the academic results during the development of the subject Morphophysiology III. Methods: A didactic methodology was applied for research abilities formation in students of the Medicine basic cycle, which included all first year students who studied the subject Morphophisiology II during the academic year 2014-15. Topics related to the content were offered for bibliography reviews under the advisory of professors fro their presentations during the last week in a scientific Event set for the occasion. Results: In four groups in with a high quality of scientific activity coincided with similar evaluation in the subject, thus considering the scientific activity a protection; in two groups the number of students with poor scientific activity coincided with a greater number of students with low academic results in Morphophisiology III. There is a crack in the process of formation of research abilities and in the application of the evaluation guides, which distorted the scores achieved by the students. Conclusion: Although there is a tendency, the exact perception of the impact of students’ scientific activity on the subject Morphophisiology III is not achieved.